1992
DOI: 10.1051/agro:19920402
|View full text |Cite
|
Sign up to set email alerts
|

Héritabilité de la résistance à la fusariose de l'épi et sélection récurrente dans une population de blé tendre

Abstract: résistance / Fusarium culmoruml blé / sélection récurrente / sélection précoce / héritabilité Summary — Heritability and recurrent selection for resistance to Fusarium head blight in winter wheat. Fifty-six S 1 families and their S 2 progeny from a winter wheat population with genic male sterility were evaluated for reaction to Fusarium head blight. Families were tested in the field using artificial inoculation. Tests were repeated over 2 years for S 1 families. Disease severity was scored on spikes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…These results are consistent with previously genetic studies of FHB resistance (Bai and Shaner 1996;. Saur and Trottet (1992) and Singh et al (1995) measured FHB resistance by visual observation and reported heritability estimates ranging from 0.66 to 0.93 under field conditions. Recently, high broad-sense heritabilities (h 2 > 0.75) for FHB resistance have been reported (Buerstmayr et al 2000).…”
Section: Fhb Assessmentsupporting
confidence: 92%
“…These results are consistent with previously genetic studies of FHB resistance (Bai and Shaner 1996;. Saur and Trottet (1992) and Singh et al (1995) measured FHB resistance by visual observation and reported heritability estimates ranging from 0.66 to 0.93 under field conditions. Recently, high broad-sense heritabilities (h 2 > 0.75) for FHB resistance have been reported (Buerstmayr et al 2000).…”
Section: Fhb Assessmentsupporting
confidence: 92%
“…They used replicated single‐spike inoculations in the field to evaluate F 6 recombinant inbred populations from crosses involving ‘Frontana’ as the resistant parent. Similarly, Saur and Trottet (1992) reported heritability estimates in the range of 0.8 to 0.9 for visual FHB symptoms using spray inoculations. These heritability estimates were derived from single‐environment experiments and are likely inflated by genotype × environment interaction.…”
Section: Discussionmentioning
confidence: 95%
“…Snijders (1990b) reported broad‐sense heritability of FHB resistance in F 2 single‐plant populations from 0.05 to 0.89. Heritability estimates by Saur and Trottet (1992) and Singh et al (1995) were in the range of 0.66 to 0.93 but were derived from single environments.…”
mentioning
confidence: 99%
“…Ils présentent alors l'intérêt d'une évalua-tion plus poussée (matériel plus fixé, caractères mesurés plus nombreux, conditions d'essais plus conformes à celles de la grande culture) ou éva-luent un plus grand nombre de cycles. D'autres relatent des expériences partant de matériel extrait de populations déjà utilisées (Burton et al, 1990 : population PII ; Hanson, 1985Hanson, et 1992 Gao, 1982, in Saur et Trottet, 1992Leemans, 1992) mais ne sont pas utilisés. Les expérimentateurs ont pu renoncer face à la difficulté à gérer le système Frey, 1989a ;Burton et al, 1983) ou font suivre les croisements simples entre parents d'un diallèle (Frey et al, 1988 ;Marocco et (Burton et al, 1990 ;Tinius et al, 1991 (Frey et al, 1988 ; et Frey, 1990 Bliss, 1991 a et 1991 b ; Tinius et al, 1991 et 1992 ; Burton et al, 1990).…”
Section: Préliminairesunclassified